Human capital and development accounting: New evidence from wage gains at migration - Lutz Hendricks; Todd Schoellman (Goethe University Frankfurt, Center for Financial Studies (CFS), 2016)
We reconsider the role for human capital in accounting for cross-country income differences. Our contribution is to bring to bear new data on the pre- and post- migration labor market experiences of immigrants to the U.S. Immigrants from poor countries experience wage gains that are only 40 percent of the GDP per worker gap, which implies that "country" accounts for 40 percent of income differences, while human capital accounts for 60 percent. Our approach handles selection by comparing the wage of the same individual in two different countries. We also provide evidence on and a correction for skill transfer.
urn:nbn:de:hebis:30:3-420754
Keywords: O11; J31; 330